Commentaires sur le rapport du Comité mixte spécial sur la réforme du Sénat - Tremblay, Arthur (Les Cahiers de droit, 1985)
In this article the author comments on the feasibility and urgency of adopting propositions from the seventh and the last chapters of the report from the Special Committee on Senate Reform. These chapters deal with the selection of senators, their mandates, the powers of a nominated senate and the internal organization of the Senate. He has choosen these reforms because they could be achieved relatively easily and quickly by the power of the Senate itself, that of the Parliament, the initiative of the Prime Minister or the senator and their political groups. Tremblay suggests that these reforms would not radically change either the essential order of things or serve to restore the image of the Senate. However, he cites the committee's non-renewable nine year mandate, the change in the number of senatorial seats and fair regional representation as in-depth reform measures which could only take place after certain constitutional modifications. The author concludes by saying that due to the present constitutional climate and the history of shelved reform reports, a modest and realistic approach to senate reform should be adopted. The reforms proposed in chapter seven of the Committee's report would be best undertaken by the Senate itself.